Benefits of Cardamom (Elettaria cardamomum (L.) Maton) and Turmeric (Curcuma longa L.) Extracts for Their Applications as Natural Anti-Inflammatory Adjuvants - Gustavo R. Cárdenas Garza; Joel H. Elizondo Luévano; Aldo F. Bazaldúa Rodríguez; Abelardo Chávez Montes; Raymundo A. Pérez Hernández; Ameyalli J. Martínez Delgado; Sonia M. López Villarreal; José Rodríguez Rodríguez; Rosa M. Sánchez Casas; Uziel Castillo Velázquez; Osvelia E. Rodríguez Luis (Plants, 2021)
The genus Zingiberaceae has been widely used for phytotherapeutic purposes in traditional medicine throughout the world for its anti-inflammatory activity. Experimental studies have established that inflammation caused by chronic infections represents a risk factor for different forms of cancer. The objective of this study was focused on determining the anti-inflammatory capacity and cytotoxic activity of aqueous extracts of Elettaria cardamomum (cardamom) and Curcuma Longa (turmeric). The extracts were obtained by maceration and, through GC-MS/MS, a total of 11 different chemical components were determined in the aqueous extract of cardamom and 7 in the extract of turmeric. The main compounds found in cardamom and turmeric were α-terpinyl acetate (54.46%) and β-turmerone (33.45%), respectively. RT-qPCR results showed significantly lower gene expression levels of innate inflammatory cytokines (IL-6 and TNF-α) compared to the control (LPS). Also, it was observed that the extracts do not possess cytotoxic activity against different cell lines, where E. cardamomum showed EC50 (µg/mL) of 473.84 (HeLa cells), 237.36 (J774A.1 cells), 257.51 (Vero E6 cells), and 431.16 (Balb/C peritoneal cells) and C. longa showed EC50 (µg/mL) of 351.17 (HeLa cells), 430.96 (J774A.1 cells), 396.24 (Vero E6 cells), and 362.86 (Balb/C peritoneal cells). The results of this research suggest that natural extracts of E. cardamomum and C. longa possess anti-inflammatory effects and no cytotoxic activity against HeLa, J774A.1, Vero E6, and Balb/C peritoneal cell lines. Finally, it was observed that the extracts also decreased nitric oxide (NO) production in peritoneal macrophages.